Phosphorylation at Thr-290 regulates Tpl2 binding to NF-κB1/p105 and Tpl2 activation and degradation by lipopolysaccharide - Cho, Jeonghee (National Academy of Sciences, 2005)
The serine–threonine protein kinase encoded by the Tpl2 protooncogene transduces Toll-like and death receptor signals in a variety of cell types and plays an important role in innate immunity and inflammation. Differential translational initiation of the Tpl2 mRNA gives rise to 58-kDa (p58) and 52-kDa (p52) isoforms. In unstimulated cells, both isoforms are stabilized and inactivated by stoichiometric binding to NF-κB1/p105. After lipopolysaccharide or TNF-α stimulation, p58 is released from p105 preferentially relative to p52. The released p58 is active but unstable and undergoes rapid degradation via the proteasome. Recent studies revealed that Tpl2 undergoes phosphorylation at Thr-290 and that phosphorylation at this site is required for activation. Here, we present evidence showing that it is the p58 isoform that is preferentially phosphorylated at Thr-290 and that phosphorylation is more efficient when p58 is complexed to p52. Because p58 is preferentially released from p105 after stimulation, we examined whether Tpl2 phosphorylation at this site controls the dissociation of the two proteins in response to external signals and the subsequent events leading to the activation of Tpl2. The results showed that lipopolysaccharide-induced Tpl2 phosphorylation at Thr-290 in macrophages promotes the release of Tpl2 from p105, contributes to the enzymatic activation of the Tpl2 kinase, and is required for the degradation of Tpl2 via the proteasome.